Diversity and ecology of araceae in the water catchment area of Ulu Sat, Kelantan, Peninsular Malaysia - Zulhazman Hamzah; E R Aweng; M A Mohamad-Faiz; A Muhamad-Azahar; H Kamarul-Ariffin; H Nor-Hizami; A K Mohammad-Firdaus; Fiffy Hanisdah Saikim; M Z Norhazlini; S Norzielawati (IOP Publishing Ltd, 2021)
Araceae or aroid is familiarly known as keladi to the locals. The purpose of this study is to assess the diversity and ecology of Araceae in the Water Catchment Area of Ulu Sat, Kelantan, Peninsular Malaysia. The random sampling method was applied. A total of 26 species from 13 genera of Araceae were recorded from the water catchment area of Ulu Sat, Machang, Kelantan, Peninsular Malaysia. This represents about 18.6% out of an estimated 140 species and 46.2% of the 28 genera of Araceae reported for Peninsular Malaysia. The result also shows that 24 species or 92.3% of the collection are the common Araceae species found in lowland dipterocarp forest in Peninsular Malaysia. However, the collection include the species recently recorded, Aglaonema cochinchinense Engl. and the endemic species, Alocasia puber (Hassk.) Schott for Peninsular Malaysia. The paper will also discuss the distribution and ecology of some important Araceae collected from this area.